2005
DOI: 10.1038/sj.jcbfm.9600244
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hyperperfusion after Carotid Endarterectomy is Associated with Preoperative Hemodynamic Impairment and Intraoperative Cerebral Ischemia

Abstract: The aim of this study was to investigate whether postoperative hyperperfusion is associated with preoperative cerebral hemodynamic impairment due to chronic ischemia and with acute cerebral ischemia during clamping of the internal carotid artery (ICA) during carotid endarterectomy (CEA). Transcranial cerebral oxygen saturation (SO 2 ) was monitored intraoperatively using near-infrared spectroscopy in 89 patients undergoing CEA for ipsilateral ICA stenosis ( > 70%). Cerebral blood flow (CBF) and cerebrovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 38 publications
6
56
0
Order By: Relevance
“…15,25) Both CEA 8,11,13,25,28) and CAS can improve CBF impairment. 12,18,29) However, hyperperfusion syndrome (HPS) has been reported after both procedures, 1,2,10,16,17,22,23) so prevention and treatment of HPS are important issues in the perioperative management of patients undergoing CAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,25) Both CEA 8,11,13,25,28) and CAS can improve CBF impairment. 12,18,29) However, hyperperfusion syndrome (HPS) has been reported after both procedures, 1,2,10,16,17,22,23) so prevention and treatment of HPS are important issues in the perioperative management of patients undergoing CAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, marked hemodynamic changes in the cerebral circulation associated with the reconstruction of the blood flow in the carotid artery may occur and may require intensive post-procedure management after CAS, 1,2,10,12,16,18,29) as seen in patients treated by CEA. 8,11,13,25,28) Therefore, mild hypertension to keep sufficient cerebral perfusion pressure is recommended in postoperative care for patients with preceding impaired cerebral circulation if adequate improvement in cerebral blood flow (CBF) is not observed after carotid revascularization. On the other hand, prompt and strict control of blood pressure within normal or slightly subnormal values should be adopted if excessive increase of the CBF is observed postoperatively in the same patient to prevent hyperperfusion syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperperfusion syndrome (associated with increased CBF compared with preoperative values) results in headache, focal seizure activity, cerebral edema, and intracerebral hemorrhage and is associated with significant mortality and morbidity. 29 Komoribayashi et al 109 reported hyperperfusion immediately after CEA in 56% of patients with reduced preoperative CVR. Another study measured concentrations of malondialdehyde-modified low-attenuation lipoprotein (MDA-LDL), a biochemical marker of oxidative damage, in serum samples and CVR measurements in 90 patients undergoing CEA.…”
Section: Hyperperfusion Syndromementioning
confidence: 99%
“…3,15,19,22) Patients with poor cerebrovascular reactivity are known to have higher risk for hyperperfusion syndrome. 12,18,23) The severity of intraoperative ischemia is also reported to be one of the predictive factors for hyperperfusion syndrome after CEA. 12) In contrast, hyperperfusion syndrome after superficial temporal arterymiddle cerebral artery (STA-MCA) anastomosis for atherosclerotic diseases is thought to be rare, since STA-MCA anastomosis usually provides low-flow revascularization.…”
Section: Introductionmentioning
confidence: 99%